2016
DOI: 10.1074/jbc.m116.725358
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase III, but Not Polymerase IV, Must Be Bound to a τ-Containing DnaX Complex to Enable Exchange into Replication Forks

Abstract: Examples of dynamic polymerase exchange have been previously characterized in model systems provided by coliphages T4 and T7. Using a dominant negative D403E polymerase (Pol) III ␣ that can form initiation complexes and sequester primer termini but not elongate, we investigated the possibility of exchange at the Escherichia coli replication fork on a rolling circle template. Unlike other systems, addition of polymerase alone did not lead to exchange. Only when D403E Pol III was bound to a -containing DnaX comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 46 publications
(64 reference statements)
1
17
1
Order By: Relevance
“…Further work is necessary to deduce whether the proposed primase-to-polymerase switch via the DnaG-induced conformational change in the helicase represents a mechanism that is regularly utilized in OF synthesis, or whether it serves as a backup mechanism to handle roadblocks and obstructions, i.e., when priming on the leading strand becomes necessary or when there are delays in the recycling of the lagging-strand polymerase. The first possibility would appear to be in strongest agreement with the recent paradigm shift in the field proposing a rather stochastic behaviour of Pol III* at the replication fork, with new Pol III*s dynamically exchanging in the replisome while DnaB remains stably associated at the fork (Geertsema and van Oijen, 2013; van Oijen and Dixon, 2015;Yuan et al, 2016;Beattie et al, 2017;Lewis et al, 2017;Graham et al, 2017;Monachino et al, 2017). Interestingly, the T7-phage employs a similar strategy of accumulation of polymerases (gp5) on the helicase fused to the primase (gp4) for prompt primer handoff (Loparo et al, 2011;Geertsema et al, 2014).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Further work is necessary to deduce whether the proposed primase-to-polymerase switch via the DnaG-induced conformational change in the helicase represents a mechanism that is regularly utilized in OF synthesis, or whether it serves as a backup mechanism to handle roadblocks and obstructions, i.e., when priming on the leading strand becomes necessary or when there are delays in the recycling of the lagging-strand polymerase. The first possibility would appear to be in strongest agreement with the recent paradigm shift in the field proposing a rather stochastic behaviour of Pol III* at the replication fork, with new Pol III*s dynamically exchanging in the replisome while DnaB remains stably associated at the fork (Geertsema and van Oijen, 2013; van Oijen and Dixon, 2015;Yuan et al, 2016;Beattie et al, 2017;Lewis et al, 2017;Graham et al, 2017;Monachino et al, 2017). Interestingly, the T7-phage employs a similar strategy of accumulation of polymerases (gp5) on the helicase fused to the primase (gp4) for prompt primer handoff (Loparo et al, 2011;Geertsema et al, 2014).…”
Section: Discussionmentioning
confidence: 56%
“…Recent advances in the field have challenged the deterministic view of the replisome as a perfectly orchestrated machine, whereby a single Pol III*, stably bound to the replication fork, replicates DNA in a strictly ordered sequence of events (van Oijen and Dixon, 2015;Graham et al, 2017). Instead, frequent turnover of the Pol III* in the replisome has been observed (Yuan et al, 2016;Beattie et al, 2017;Lewis et al, 2017), suggesting that the helicase acts as the central organizing structure of the replisome as opposed to the polymerase. An explanation for this surprising level of plasticity can be found in the network of weak interactions that enable polymerases from solution to eventually replace those at the fork (Geertsema and van Oijen, 2013;Lewis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…DnaE is displaced by PolC, and this must occur early in vivo , because DnaE is error-prone and efficient at lesion bypass ( 15 , 16 ). Previous studies showed that PolC early gains access to primers synthesized by the DnaG–DnaE complex on the lagging-strand ( 20 , 59 ). However, the exact mechanism of polymerase switch is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the introduction of high concentrations of catalytically dead Pol III* (still able to bind primed DNA) inhibits ongoing replication (Yuan et al, 2016). Reconciling these different observations, we here demonstrate the presence of a novel exchange mechanism that allows Pol III* to remain stably associated with the replisome under conditions of high dilution, yet facilitates rapid exchange at nanomolar concentrations.…”
Section: Introductionmentioning
confidence: 99%